Bacterial cellulose-based scaffold with in-situ cationic micelle modification for urethral stricture disease: Sustained drug components release, cytokines recruitment, and bacterial microenvironment regulation - Zhenpeng Zhu; Jianming Zhao; Xing Ji; Weimin Hu; Wenyuan Leng; Chunru Xu; Xiaoyu Li; Kunlin Yang; Xuesong Li; Yudong Zheng; Jian Lin (Bioactive Materials, 2025)
The treatment of urethral stricture disease and the prevention of restenosis present considerable challenges in the field of urology. Tissue-engineered materials, particularly bacterial cellulose scaffolds, have emerged as promising solutions due to their abundant sources, excellent mechanical properties, and biocompatibility. However, for attaining superior treatment for patients with USD, further modification of bacterial cellulose is necessary. We have fabricated a dual-network scaffold with enhanced antibacterial properties and cytokines absorption ability through in-situ polymerization of cationic polyurethane micelles and cyclodextrin on oxidized bacterial cellulose. This scaffold also enables long-term sustained release of loaded drug components. Animal model studies have confirmed that this scaffold can achieve urethral repair outcomes comparable to those of normal urethral tissue. This innovative material provides a robust foundation for advancing new concepts and methodologies in the treatment of urethral stricture disease, potentially transforming clinical approaches to this challenging condition.